2016
DOI: 10.3389/fonc.2016.00071
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study to Identify Radiomics Classifiers for Lung Cancer Histology

Abstract: BackgroundRadiomics can quantify tumor phenotypic characteristics non-invasively by applying feature algorithms to medical imaging data. In this study of lung cancer patients, we investigated the association between radiomic features and the tumor histologic subtypes (adenocarcinoma and squamous cell carcinoma). Furthermore, in order to predict histologic subtypes, we employed machine-learning methods and independently evaluated their prediction performance.MethodsTwo independent radiomic cohorts with a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
238
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(264 citation statements)
references
References 57 publications
8
238
0
Order By: Relevance
“…ML holds also a great potential for dealing with "big data" generated by hybrid imaging methods [280]. For example, ML has been successfully applied in hybrid imaging to predict survival [283], treatment outcome [284], and tumor grading [285]. Furthermore, unsupervised ML allows the identification of breast cancer subtypes [286].…”
Section: Image-derived Prediction Modelsmentioning
confidence: 99%
“…ML holds also a great potential for dealing with "big data" generated by hybrid imaging methods [280]. For example, ML has been successfully applied in hybrid imaging to predict survival [283], treatment outcome [284], and tumor grading [285]. Furthermore, unsupervised ML allows the identification of breast cancer subtypes [286].…”
Section: Image-derived Prediction Modelsmentioning
confidence: 99%
“…Accordingly, promising results in the field of treatment outcome [161], therapy response [156,162], survival [163][164][165][166] as well prognostic stratification [167] have been proposed. Several studies perform conventional correlation analysis [156,160,165,168,169], as well as robust machine learning evaluation [10,170,171] of textural features to characterize tumors in vivo. An oncological review of PET-based radiomic approaches concluded that it is a promising method for personalized medicine as it can enhance cancer management [172].…”
Section: Radiomicsmentioning
confidence: 99%
“…Within oncology, multiple efforts have successfully explored radiomics tools for assisting clinical decision making related to the diagnosis and risk stratification of different cancers 15,16 . For example, studies in non-small-cell lung cancer (NSCLC) used radiomics to predict distant metastasis in lung adenocarcinoma 17 and tumour histological subtypes 18 as well as disease recurrence 19 , somatic mutations 20 , gene-expression profiles 21 and overall survival 22 . Such findings have motivated an exploration of the clinical utility of AI-generated biomarkers based on standard-of-care radiographic images 23 — with the ultimate hope of better supporting radiologists in disease diagnosis, imaging quality optimization, data visualization, response assessment and report generation.…”
mentioning
confidence: 99%